2014
DOI: 10.1186/1756-0500-7-48
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of a sample of type 2 diabetic patients with obesity or overweight and at cardiovascular risk: a cross sectional study in Spain

Abstract: BackgroundThe multifactorial control of diabetes relies on interventions that provide patients with the best knowledge and resources available. The objective of this research was to analyze the clinical characteristics of a sample of people with type 2 diabetes at high cardiovascular risk, and establish possible links between disease control, family history and lifestyle, to improve the quality of interventions. Family history, lifestyle habits, blood pressure, anthropometric data and laboratory tests were ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Obesity is considered to be a significant independent cardiovascular risk factor, but both, obesity and DM are not included in the equation of cardiovascular risk assessment, but only as additive variable. A link between obesity and cardiovascular risk in DM patients is shown by a study which concluded that patients with poor nutrition, lack of physical activity have higher HbA1c values and that they constitute the largest number of patients with very high cardiovascular risk ( 14 ). “Look AHEAD (Action for Health in Diabetes)” is a great clinical study of the effects of persistent weight loss on glycemia and the prevention of CVD and vascular incidents in patients with DM type 2.…”
Section: Discussionmentioning
confidence: 99%
“…Obesity is considered to be a significant independent cardiovascular risk factor, but both, obesity and DM are not included in the equation of cardiovascular risk assessment, but only as additive variable. A link between obesity and cardiovascular risk in DM patients is shown by a study which concluded that patients with poor nutrition, lack of physical activity have higher HbA1c values and that they constitute the largest number of patients with very high cardiovascular risk ( 14 ). “Look AHEAD (Action for Health in Diabetes)” is a great clinical study of the effects of persistent weight loss on glycemia and the prevention of CVD and vascular incidents in patients with DM type 2.…”
Section: Discussionmentioning
confidence: 99%
“…However, only 50% were treated with OAPs and/or OACs. On the other hand, Lucha-López et al described a sample of 38 Spanish T2DM subjects with overweight and obesity, and ASA was used by 87% of participants [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Overweight or obese in patients with T2D were estimated to be around 86% in the United Kingdom within 3637 patients [2]. Obesity with T2D [3] and hyperlipidemia [4] contributes to worse cardiovascular risk factor without weight maintenance management.…”
Section: Introductionmentioning
confidence: 99%